Portrait of the Empress Elizaveta Petrovna by Georg Kaspar von Prenner (1754, State Tretyakov gallery) and European Tradition of Portraits in Flower Wreath - Skvortcova, Ekaterina A. (Actual Problems of Theory and History of Art, 2020)
This research was supported by the grant of the President of the Russian Federation for theyoung PhDs no. МК–1510.2019.6 “Female and Children Images in Discourse of Imperial Power: On the Example of 18th-Century Russian Art”.“Portrait of Empress Elizaveta Petrovna” by G. K. von Prenner is the only 18th-century secular easel portrait in a painted flower frame in Russian art. “Complimentary symbolism” of flowers was deciphered by L. Markina who also indicated portrait’s link to European tradition of depicting Madonna in floral wreath. However, a more important context of European secular portraits surrounded with flower garlands has so far been completely ignored. Neither have these portraits been a subject of special examination in European art history. The paper offers an overview of such European portraits of the last quarter of the 17th — early 18th centuries. Upon their background the portrait of Elizaveta Petrovna demonstrates a unique combination of exclusively sumptuous frame and significance of a portrait image — a faultless artistic decision which transmits state and international status of a model. The portrait preserves sacramental political connotations traditionally inherent to garland painting in Dutch and Flemish art chiming with the ideas manifested inliterature of Elizabethan time in which the metaphor of the garden epitomized the idea of peaceful prosperity of the Empire. On the other hand, Prenner’s portrait floral frame is also an accessory accentuating beauty of a model as it was in late 17th-century French samples. Prenner could have special appreciation of garland framesas he was familiar with the gallery of the Emperor Carl VI in Stallburg in Vienna which had a special room featuring exclusively flower still-lifes and pictures  in flower frames (counting some portraits). How actual the motif turned out to be at the court of Empress Elizaveta demonstrates its widespread in other kinds of art (triumphal arches, painted plafonds, molded interior decoration, applied art, engraving).
Keywords: G. K. von Prenner; 18th-century Russian art; 17th–18th-century European art; painting; Rossica; secular portrait in flower frame; garland paintings; iconography of Empress Elizaveta Petrovna